INTEGRATION OF INSTITUONAL SPATIAL PROJECTS INTO DEVELOPMENT PLANS AND PROBLEMS - Ozturk, Derya; Kilic, Fatmagul (YILDIZ TECHNICAL UNIV, 2013)
Detection thresholds limiting and directing the urban development in planning is of great importance to generate development plans based on the balance of protection and use. Preparation of natural and institutional thresholds and constraints that constitute the basis in planning and integration with plans correctly are very important to make the right planning decisions. In present study to analyze in detail the problems faced in the integration of institution views with planning process while development plans are prepared, this study has been limited to one institution alone. In the preparation of development plans flood protection boundaries, irrigation projects and similar data that must be obtained from State Hydraulic Works (DSI), legal regulations related to data production and integration with plans and experienced problems have been elaborated; insufficiencies in the quality of base maps employed in studies and problems that arise when plan decisions that lack institution's approval or clash with the institution's views are employed shall be explored at length.
Keywords: Development plan; threshold; flood protection boundary; irrigation project; Engineering